A Comprehensive Review on Methodologies Employed for Visual Evoked Potentials. (29th February 2016) - Kothari, Ruchi; Bokariya, Pradeep; Singh, Smita; Singh, Ramji
Abstract : Visual information is fundamental to how we appreciate our environment and interact with others. The visual evoked potential (VEP) is among those evoked potentials that are the bioelectric signals generated in the striate and extrastriate cortex when the retina is stimulated with light which can be recorded from the scalp electrodes. In the current paper, we provide an overview of the various modalities, techniques, and methodologies which have been employed for visual evoked potentials over the years. In the first part of the paper, we cast a cursory glance on the historical aspect of evoked potentials. Then the growing clinical significance and advantages of VEPs in clinical disorders have been briefly described, followed by the discussion on the earlier and currently available methods for VEPs based on the studies in the past and recent times. Next, we mention the standards and protocols laid down by the authorized agencies. We then summarize the recently developed techniques for VEP. In the concluding section, we lay down prospective research directives related to fundamental and applied aspects of VEPs as well as offering perspectives for further research to stimulate inquiry into the role of visual evoked potentials in visual processing impairment related disorders.